DIRECTIONS OF THE DEVELOPMENT OF THE LOCAL HISTORY WORK AT MODERN PEDAGOGICAL COLLEGES - Крамская, Зоя (SWorldJournal, 2021)
In the conditions of reforming the primary education the organization of local history work in the New Ukrainian school and preparation the students of pedagogical colleges for it acquire special urgency. As it is evidenced by our analysis of the situatio